(untitled) (GYMNASIUM, 2009)
In this study, we used data collected from students of two European academic campuses - Gottingen (Germany) and Bacău (Romania) to examine and compare problems concerning their health status and scholar success. We compared students’ self-reported emotional-behavioural problems and their physical and psychic status with their ability to be successful in university across the two samples. Consistent with previous research, we found that German students reported more internalizing and externalizing problems than their Romanians peers did. The identification of similarities, differences, but also the specific aspects of the health status between German and Romanian students was made mostly regarding the risk factors on health. In this study, the socio-cultural particularities constitute the independent variable which can influence the physical and psychic health. The findings are discussed in relation to an intricate model that shape patterns of academic investment.